Caracterização de professores de atendimento educacional especializado de uma rede municipal de ensino frente ao repertório inicial sobre recursos e sistemas de comunicação alternativa - Botteon, Beatriz Giordani (Universidade Federal de São Carlos, 2021)
Alternative and Extended Communication (AEC) is an area dedicated to organizing resources and communication strategies that are essentials for non-oralized children or those with little functional speech, enabling broad participation in their daily activities. Through these resources, it is possible to include students with disabilities and communication needs in various pedagogical activities, and to expand the skills and abilities stimulated by teachers in the teaching-learning process. The objective of the study was to characterize the teachers of the Specialized Educational Service (SES), working in a Municipal Education Network, regarding their initial repertoire in relation to the Alternative Communication resources and systems. The specific objectives were to investigate the previous formative experiences carried out by teachers, practices experienced in everyday school life with this type of resource and the possible challenges encountered in the teaching-learning process of students with communicative difficulties. Twenty seven teachers of SES from an Education network of a city located in the interior of São Paulo, participated in the research through the online application of a questionnaire built for the study. After conducting the preliminary ethical procedures, the questionnaire was made available online between the months of November and December 2020 to a group of SES teachers who were starting a training course in technology resources for remote education offered by UFSCar University. The data were analyzed in a descriptive, quantitative and qualitative way. The findings identified that SES teachers still have little knowledge about AEC technologies and resources and that most have difficulties to implement in practice, but that they understand the benefits of these resources to students. It is concluded that the AEC is fundamental for the teaching-learning of the student within the school context, but for this use to be effective, the continuing education of these teachers is necessary. Therefore, it understands the power of partnerships with others as well professionals such as occupational therapists and speech therapists so that the implementation can happen in the best possible way.
Characterization of specialized education teachers from a municipal school system in light of the initial repertoire of augmentative and alternative communication systems.
Keywords: Terapia ocupacional; Comunicação alternativa; Atendimento educacional especializado; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO